2008
DOI: 10.1387/ijdb.072477ea
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and expression analysis of foxj1 and foxj1.2 in zebrafish embryos

Abstract: In this report, we present the isolation and identification of a zebrafish homolog of the winged helix\forkhead transcription factor Foxj1. Foxj1 was identified in other species but not in zebrafish. Foxj1 was shown in mice to be required in ciliogenesis and left-right asymmetry establishment. Here we present a spatio-temporal expression pattern of zebrafish foxj1, showing that this gene is expressed in dorsal forerunner cells, Kupffer's vesicle, the floor plate, pronephric ducts and kidney. This expression pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 36 publications
0
19
0
Order By: Relevance
“…sox17 and foxj1a are expressed in the zebrafish DFCs, and foxj1a functions to promote cilia formation in various tissues (Aamar and Dawid, 2008;Amack and Yost, 2004;Yu et al, 2008;Tian et al, 2009). We found that sox17 and foxj1a expression levels in DFC -cat1MO , DFC -cat2MO or DFC…”
Section: Dfcs-specific Ctnnb1/2 Activity Regulates Distinct Transcripmentioning
confidence: 73%
“…sox17 and foxj1a are expressed in the zebrafish DFCs, and foxj1a functions to promote cilia formation in various tissues (Aamar and Dawid, 2008;Amack and Yost, 2004;Yu et al, 2008;Tian et al, 2009). We found that sox17 and foxj1a expression levels in DFC -cat1MO , DFC -cat2MO or DFC…”
Section: Dfcs-specific Ctnnb1/2 Activity Regulates Distinct Transcripmentioning
confidence: 73%
“…The expression of ciliogenic transcription factor foxj1a is initiated in DFCs, becomes robust towards the end of gastrulation (Aamar and Dawid, 2008;Yu et al, 2008;Tian et al, 2009) and is then gradually downregulated in KV (A.C., unpublished). The correlation between foxj1a expression in DFCs/KV lineage and the temporal requirement for Wnt signaling in KV ciliogenesis prompted us to examine foxj1a transcripts.…”
Section: Non-transgenic Siblings (Gfp-)mentioning
confidence: 99%
“…Two distinct foxj1 genes, foxj1a and foxj1b, have been identified in zebrafish tissues. Their expression is mutually exclusive in KV (foxj1a) and OVs (foxj1b), but partially overlaps in PDs and FP (Aamar and Dawid, 2008;Yu et al, 2008). Depletion of foxj1a results in abnormal LR asymmetry and renal cyst formation, whereas depletion of foxj1b leads to otolith disorganization (Stubbs et al, 2008;Yu et al, 2008;Yu et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Among the two paralogous foxj1 genes in the zebrafish genome, foxj1b is expressed in cells of the otic vesicle (Aamar and Dawid, 2008;Tian et al, 2009a;Yu et al, 2008). Transcription of foxj1b initiates as early as 10 hpf, and at this stage is observed throughout the nascent otic placode (Fig.…”
Section: Foxj1b Expression and The Distribution Of Motile Cilia In Thmentioning
confidence: 99%